Korelasi Antara Tingkat Prolaktin Dan Oksitosin Dengan Komposisi Mineral Air Susu Ibu (Asi) Pada Ibu Menyusui: Sebuah Studi Observasional - Sari, Silvie Permata; Herayono, Febby; Arman, Eliza; Nurhasanah Amir, Ade (Jurnal Kesehatan Medika Saintika, 2024)
This study aims to investigate the relationship between prolactin and oxytocin hormone levels with the mineral composition of breast milk in breastfeeding mothers through an observational study approach. The urgency of this study lies in the importance of understanding the hormonal factors that affect the mineral composition of breast milk, which can provide important knowledge for health practitioners in improving the quality and quantity of breast milk to support maternal and infant health. This study will use an observational study method where prolactin and oxytocin levels will be measured in the blood of breastfeeding mothers who have 3-month-old babies using the ELISA method, while the mineral composition of breast milk will be comprehensively evaluated using the AAS method. Data will be collected through direct observation and blood and breast milk sampling from mothers who have given their consent and passed the research ethics test. Statistical analysis with correlation tests will be carried out to explore the correlation between prolactin and oxytocin hormone levels with the mineral composition of breast milk. The targeted output of this study is a deeper understanding of the role of prolactin and oxytocin in the mineral composition of breast milk and identification of the relationship between these hormones and the characteristics of breast milk. The results of this study are expected to provide a stronger basis for the development of intervention strategies aimed at increasing breast milk production and maternal and infant health. In addition, the findings of this study are also expected to provide a significant contribution to the scientific literature in the field of maternal and infant health, as well as provide a basis for improving clinical practice in caring for mothers and infants during the breastfeeding period. The results of the correlation test showed that there was no significant relationship between Prolactin and Ca (Calcium) levels with a correlation coefficient of -0.314 and a p value of 0.091. However, a very strong correlation was found between Prolactin and Zn (Zinc) with a correlation coefficient of 0.601 and a p value of 0.000, indicating a significant positive relationship between the two. Meanwhile, there was no significant relationship between Oxytocin and Ca (Calcium) with a correlation coefficient of -0.091 and a p value of 0.633. Conversely, there was a moderate relationship between Oxytocin and Zn (Zinc) with a correlation coefficient of 0.457 and a p value of 0.011, indicating a significant positive correlation between the two variables. Thus, the results of this study found a significant relationship between prolactin and zinc and oxytocin and zinc, but not with calcium. The TKT of this study was 3. The research output was published in the national journal.Keywords: Hormones, Prolactin, Oxytocin, Breast milk (ASI)